INTERNATIONAL STUDENTS IN THE UNIVERSITY EDUCATIONAL ENVIRONMENT IN THE CONTEXT OF THE WAR IN UKRAINE: RISKS OF EXCLUSION AND PROVIDING WELL-BEING (Bulletin of Taras Shevchenko National University of Kyiv. Social Work, 2025)
Background. The article is a theoretical analysis of the situation of risks of social exclusion of foreign students in the educational environment of the university caused by the threats of war and wartime in Ukraine.  The purpose of the article is to actualise the problem of a safe university educational environment, to present a theoretical model of conditions for preventing social exclusion of foreign students in it.Methods: analysis, synthesis and generalization of published Ukrainian and foreign materials on the phenomenon under study, prognostic analysis and modelling.  Results. In the context of social crises and upheavals that Ukrainian society has experienced in recent years (starting with the Covid-19 epidemic and continuing with military events in the country), significant changes are taking place in the educational policy of universities. Threats and risks are faced by both individual actors in the educational environment and certain social groups that may potentially experience social exclusion and isolation. These groups include international students who have found themselves in a situation of uncertainty, stress, threat, and unpredictability since the outbreak of war, and whose urgent task is to complete their studies at universities and maintain their physical and mental health. The analysis of Ukrainian and foreign practices of supporting the well-being of foreign students in times of crisis indicates the need to create special conditions for the educational environment, which have a multi-component structure and levels of support.Conclusions. The developed theoretical model of the structural components of the university educational environment contains five components: academic, information and communication, infrastructure, professional and socialization, and socio-cultural, each of which is endowed with conditions and opportunities for the development of the personality of an international student, his/her professional socialization and in every way contributes to his/her active inclusion and participation, which is a condition for ensuring psychosocial well-being and counteracting social exclusion.
Keywords: international student; psychosocial well-being; social exclusion; theoretical model of educational environment; university educational environment